Comparing the Structure of Scientific Articles in the Tatar and English Languages - Anvarovna, Albina Bilyalova; Valeeva, Aigul Rafailevna (Journal of History Culture and Art Research, 2017)
It is widely accepted that science plays a key role in the development of society, thus domestic scientists and scientific workers face the necessity to study foreign scientific articles, as well as the necessity to share results of their researches worldwide. Although their attempts to publish articles abroad often turn out to be unsuccessful. This study examines the structure of scientific articles in the Tatar and English languages. At first scientific articles in both languages were selected. Then the articles were scanned, analyzed and compared in both languages. It was noted that Abstract and Introduction in both languages are alike with some distinguishing features. Further research resulted in the fact that Methods and Results referring to separate sections in the English article are interwoven into one unity in the Tatar counterpart. Besides the Tatar article can omit some sections presented in the English one. We conclude that the structure of Tatar and English scientific articles are different; that means this could be a possible reason of domestic scientists’ failures in publishing their researches abroad. The results of this study are compiled for the possible use by Tatar scientific workers, university teachers or teachers educating in Tatar in order to improve their Academic writing abilities in English.